Architecture, landscape, and design in post-mining territories (Routledge, 2026)
This edited collection explores how architects, planners, and landscape architects can engage with former mining sites and communities.Chapters investigate how to move from an extractivist system towards a territorialist project, working towards the reappropriation of territorial resources after centuries of subordination of local and immigrant populations. The first part reviews cases from European sites, including examples from France, Germany, and Romania that highlight intangible heritage as the subject of a territorial project. A special focus is placed on the coalfields of northern France, a UNESCO World Heritage site since 2012, where many experimental projects are being carried out. The second part explores the great American landscapes transformed by the extractive industry in the United States, Brazil, and Chile. Fully illustrated throughout, this book features photos showcasing architectural and landscape achievements, as well as drawings of future projects. Contributors respond to the design challenges of post-mining landscapes, foreshadowing new and varied transformative horizons. The cases present a rich and articulate collection of 'on-the-ground' projects.This book is essential for practitioners and students of architecture and urban planning, as well as associations and political and technical actors in post-mining communities.
Keywords: Abandoned mined lands reclamation.; elektronické knihy; electronic books